Arabidopsis CSLD5 Functions in Cell Plate Formation in a Cell Cycle-Dependent Manner. Issue 7 (27th June 2016) - Gu, Fangwei; Bringmann, Martin; Combs, Jonathon R.; Yang, Jiyuan; Bergmann, Dominique C.; Nielsen, Erik
Abstract : Cell cycle-regulated CSLD5 provides essential cell wall synthase activity for cell plate formation during cytokinesis. Abstract: In plants, the presence of a load-bearing cell wall presents unique challenges during cell division. Unlike other eukaryotes, which undergo contractile cytokinesis upon completion of mitosis, plants instead synthesize and assemble a new dividing cell wall to separate newly formed daughter cells. Here, we mine transcriptome data from individual cell types in the Arabidopsis thaliana stomatal lineage and identify CSLD5, a member of the Cellulose Synthase Like-D family, as a cell wall biosynthesis enzyme uniquely enriched in rapidly dividing cell populations. We further show that CSLD5 is a direct target of SPEECHLESS, the master transcriptional regulator of these divisions during stomatal development. Using a combination of genetic analysis and in vivo localization of fluorescently tagged fusion proteins, we show that CSLD5 preferentially accumulates in dividing plant cells where it participates in the construction of newly forming cell plates. We show that CSLD5 is an unstable protein that is rapidly degraded upon completion of cell division and that the protein turnover characteristics of CSLD5 are altered in ccs52a2 mutants, indicating that CSLD5 turnover may be regulated by a cell cycle-associated E3-ubiquitin ligase, the anaphase-promoting complex.